(untitled) (Experimental biology, 2025)
The article presents an analysis of the spatio-temporal distribution of the fauna of birds of prey in the urbanized areas of southwestern Kazakhstan based on the results of avifauna surveys in Kyzylorda. Eight species of birds of prey were recorded, including the Circus cyaneus, Circus aeroginosus, Accipiter nisus, Buteo rufinus, Buteo buteo, Aqulia nipalensis, Falco subbuteo, Falco tinnunculus. The probability of birds of prey habitation was negatively associated with dense urban low-rise buildings with limited greenery in the outlying and new parts of the city. At the same time, dense urban development with little or no greenery in the old central part of the city provides comfortable conditions for the habitation (food supply, nesting station) of the common kestrel. The probability of habitation of birds of prey was positively associated with wastelands and the floodplain of the Syr Darya River with small groups of trees and/or shrubs. The environs of the solid waste landfill located on the north-eastern outskirts of the city serve as a food supply for the long-legged buzzard and common buzzard, and the common buzzard, steppe eagle and common kestrel live on the territory of the airport. The most numerous bird recorded in the urbanized landscapes of Kyzylorda is the rock pigeon. Based on this study, we would recommend that enterprises (grain storage, airport) and local executive bodies interested in preserving birds of prey and regulating the number of rock dove on their territory and around it, preserve or plant more native vegetation and shrubs and preserve areas with green spaces.